2017
DOI: 10.3846/13923730.2017.1381644
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Drivers of Chinese Labour Loyalty in International Construction Projects

Abstract: Organization performance is becoming ever more dependent on employee loyalty in the international construction projects. However, the improvement of construction labour loyalty on construction sites remains a largely neglected measure for reducing their turnover and improving their productivity. The purpose of this study was to quantitatively investigate the managerial drivers of labour loyalty, including macro-environment of the project host country, organizational living environment, job system, rewards, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 52 publications
1
13
0
1
Order By: Relevance
“…One of the job-related factors that linked to turnover could be the workload. Employee loyalty can be from a reasonable workload distribution (Zhu, Zeng, Li, Zhu, & Zhang, 2017). Through an exciting job designed to reduce specific preferences that involve employee health issues such as exposure to mechanical settings (Jebens et al, 2014) and proper coordination of work to enhance motivation (Rojas, 2013) development of exciting job design strategy can succeed.…”
Section: Employee Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the job-related factors that linked to turnover could be the workload. Employee loyalty can be from a reasonable workload distribution (Zhu, Zeng, Li, Zhu, & Zhang, 2017). Through an exciting job designed to reduce specific preferences that involve employee health issues such as exposure to mechanical settings (Jebens et al, 2014) and proper coordination of work to enhance motivation (Rojas, 2013) development of exciting job design strategy can succeed.…”
Section: Employee Engagementmentioning
confidence: 99%
“…The findings concluded that communication could be treated differently among different occupational groups within the construction domain. In Zhu et al (2017) who explore the construction workers utilise communication to personal interest (i.e., organisation HRM practices), which may affect their loyalty in the long run. Communication has been confirmed to correlate with job satisfaction, which contributes to turnover intention negatively amidst a sample of managerial and technical staff (Du et al, 2006).…”
Section: Communication Skillsmentioning
confidence: 99%
“…Lingard et al, (2007) prescribed attaining a balance between the demand of work and life through alternative working hours; compressed work-week, which gained positive feedback from the sample Job Related -One job-related factor involved in turnover could be the workload. Job system that focuses on reasonable workload promotes loyalty (Zhu, Zeng, Li, Zhu, & Zhang, 2017). This notion is supported through the interesting job that is designed to reduce specific preferences, such as exposure to mechanical settings (Jebensa et al, 2014) and proper coordination of work to enhance motivation (Rojas, 2013).…”
Section: Employee Engagementmentioning
confidence: 99%
“…The findings concluded that communication could be treated differently among different occupational groups within the construction domain. According to (Zhu et al, 2017), this factor contributes to only personal interests. Communication has been confirmed to have a correlation with job satisfaction, which contributes to turnover intention negatively amidst sample of managerial and technical staff (Du et al, 2006).…”
Section: Communication Skillsmentioning
confidence: 99%
See 1 more Smart Citation